2011
DOI: 10.5326/jaaha-ms-5681
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical Antiseptic Efficacy of Chlorhexidine Diacetate and Providone-Iodine in the Canine Preputial Cavity

Abstract: Antiseptic flushing of the canine prepuce and its exclusion from the surgical field are recommended before abdominal surgery to reduce the risk of bacterial contamination. The authors cultured the preputial cavity of 60 dogs prior to and following flushing with 0.05% chlorhexidine diacetate, 1% povidone-iodine, or 0.9% saline control. Bacterial growth was evaluated using a semiquantitative method, and bacterial organisms were subsequently identified. There were no significant differences between povidone-iodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
11
1
1
Order By: Relevance
“…In veterinary medicine there is no agreement on which biocide has the greatest efficacy in reducing the skin microbiota, aiming at preventing SSI development [ 4 – 6 ]. In addition, different skin asepsis protocols may be adopted according to the location of surgery in dogs [ 7 9 ]. For instance, in bitches undergoing ovariohysterectomy, 0.3% stabilized glutaraldehyde and alcohol (SG + A), 0.3% SG and water, and 4% chlorhexidine gluconate tincture revealed to be equally effective [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In veterinary medicine there is no agreement on which biocide has the greatest efficacy in reducing the skin microbiota, aiming at preventing SSI development [ 4 – 6 ]. In addition, different skin asepsis protocols may be adopted according to the location of surgery in dogs [ 7 9 ]. For instance, in bitches undergoing ovariohysterectomy, 0.3% stabilized glutaraldehyde and alcohol (SG + A), 0.3% SG and water, and 4% chlorhexidine gluconate tincture revealed to be equally effective [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The skin was prepped with povidone iodine scrub in a series of three scrubs. The prepucial fornix was lavaged with either 1% povidone iodine solution, or 0.05% chlorhexidine solution . The dog was then positioned on the operating table in dorsal recumbency with the hind limbs in extension (Fig ).…”
Section: Methodsmentioning
confidence: 99%
“…Swelling was negatively correlated with microbial load; that is, very obvious swelling was present in sites with T1 swabs and catheters that tested negative to microbial culture. Thus, swelling in our sample has been hypothesized to be the result of the corrosiveness and tissue irritating effects of iodine, even if its available concentration in povidone-iodine is very low [22,25]; it has been reported that the development of acute contact dermatitis has an incidence as high as 50% in patients treated with povidone-iodine scrubbing in dogs [26]. Another possible explanation would be a local immune response after tissue damage during catheter placement: This would explain why horses with swelling were less likely to have positive bacterial cultures.…”
Section: Timementioning
confidence: 98%